(untitled) (International Journal of Engineering Management Science, 2024)
This review paper examines the strength parameters of crimped steel fibers in concrete. The study investigates various types of crimped steel fibers available in the market and reviews studies on their tensile, compressive, and flexural strength properties. Factors influencing these strength parameters, such as fiber geometry, aspect ratio, and volume fraction, are discussed. Experimental methods for determining these parameters are described, along with challenges and limitations associated with these methods. Applications of crimped steel fibers in concrete construction are highlighted, emphasizing their benefits in terms of strength enhancement and durability improvement. The review concludes with a summary of common findings and trends observed in the literature.